The Involvement of Caspases in Neuroinflammation and Neuronal Apoptosis in Chronic Pain and Potential Therapeutic Targets - Zhang, Haoyue; Li, Nan; Li, Ziping; Li, Yize; Yu, Yonghao; Zhang, Linlin (Frontiers in Pharmacology, 2022)
Chronic pain is a common, complex and unpleasant sensation following nerve injury, tissue trauma, inflammatory diseases, infection and cancer. It affects up to 25% of adults and is increasingly recognized as the leading cause of distress, disability and disease burden globally. Chronic pain is often refractory to most current analgesics, thus emphasizing the requirement for improved therapeutic medications. It is of great importance to elucidate the specific pathogenesis of chronic pain with different etiologies. Recent progress has advanced our understanding in the contribution of neuroinflammation and glial cells (microglia and astrocyte) activation in the plasticity of excitatory nociceptive synapses and the development of chronic pain phenotypes. Oxidative stress-associated neuronal apoptosis is also identified to be a pivotal step for central pain sensitization. The family of aspartate-specific cysteine proteases (Caspases) has been well known to be key signaling molecules for inflammation and apoptosis in several neurological conditions. Recent studies have highlighted the unconventional and emerging role of caspases in microgliosis, astrocytes morphogenesis, chemokines release, cytokines secretion and neuronal apoptosis in initiating and maintaining synaptogenesis, synaptic strength and signal transduction in persistent pain hypersensitivity, suggesting the possibility of targeting caspases pathway for prevention and treatment of chronic pain. In this review, we will discuss and summarize the advances in the distinctive properties of caspases family in the pathophysiology of chronic pain, especially in neuropathic pain, inflammatory pain, cancer pain and musculoskeletal pain, with the aim to find the promising therapeutic candidates for the resolution of chronic pain to better manage patients undergoing chronic pain in clinics.